Solar-powered portable apparatus for extracting water from air using desiccant solution. (April 2018) - Talaat, M.A.; Awad, M.M.; Zeidan, E.B.; Hamed, A.M.
Abstract: In this paper, experimental and theoretical study of a portable apparatus for extracting water from atmospheric air is presented. The experimental water-extraction unit is designed, manufactured, and tested at the Faculty of Engineering, Mansoura University, Egypt (latitude 31.0409 N and longitude 31.3785 E). The unit extracts water from atmospheric air by using solar energy as the heating source and Calcium Chloride (CaCl2 ) solution as desiccant material. The unit consists of double-faced conical-finned absorber (64 cm diameter and 64 cm height), double-faced conical transparent surface (68 cm diameter and 68 cm height). The unit is provided with a telescopic stick (carrier), and base. At night, the conical absorber which is made from cloth layer impregnated with desiccant solution is exposed to atmospheric air to allow Calcium Chloride solution to absorb moisture. During daytime, the absorber is covered with the tightly-closed double-faced conical transparent surface which is exposed to solar radiation. As solar energy increases the absorber temperature, the absorbed vapor evaporates from the solution and condenses on the surface. The condensate is collected in a bottle through a hose. Radiation intensity, temperature, cover temperature, ambient temperature, and productivity are recorded at a number of different operating days year-round. The measured accumulated productivity is found to range from 0.3295 to 0.6310 kg/m 2 /day. Highlights: Performance of portable solar powered water generator is investigated. Experiments are carried out at different weather conditions. System efficiency up to 22.56% could be reached. System productivity is affected by weather fluctuation.